1990
DOI: 10.1099/0022-1317-71-10-2391
|View full text |Cite
|
Sign up to set email alerts
|

Murine cytotoxic T lymphocytes specific for herpes simplex virus type 1 recognize the immediate early protein ICP4 but not ICP0

Abstract: Vaccinia virus recombinants expressing the herpes simplex virus type 1 (HSV-1) genes encoding ICP0 or ICP4 were used to identify the precise target antigen(s) of murine anti-viral cytotoxic T lymphocytes (CTL) specific for the non-structural immediate early proteins. These studies revealed that HSV-l-specific CTL, restricted to class I major histocompatibility complex genes of the H-2 k haplotype but not the H-2 d or H-2 b haplotypes, would lyse autologous cells expressing ICP4. HSV-l-specific CTL derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 36 publications
(23 reference statements)
1
27
0
Order By: Relevance
“…In mouse models, neutralizing antibodies only partially protect against HSV-1 infection and the clearance of virus-infected cells is uniformly associated with HSV-1-specific cytotoxic T lymphocytes (CTL). 21 In contrast to neutralizing antibodies, CTL react not only against envelope glycoproteins, but also against immediate-early viral proteins, [23][24][25] which are expressed early in infection even with nonreplicative HSV-1 mutants. The CTL response to the vector and the transgenes probably did not limit the period of transgene expression in our model, as infection of D74 glioma cells with hrR3 did not lead to a productive infection and the expression of transgenes, lacZ and HSVtk, which are transcribed from early viral promotors, was probably shut down before the CTL response was effective.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models, neutralizing antibodies only partially protect against HSV-1 infection and the clearance of virus-infected cells is uniformly associated with HSV-1-specific cytotoxic T lymphocytes (CTL). 21 In contrast to neutralizing antibodies, CTL react not only against envelope glycoproteins, but also against immediate-early viral proteins, [23][24][25] which are expressed early in infection even with nonreplicative HSV-1 mutants. The CTL response to the vector and the transgenes probably did not limit the period of transgene expression in our model, as infection of D74 glioma cells with hrR3 did not lead to a productive infection and the expression of transgenes, lacZ and HSVtk, which are transcribed from early viral promotors, was probably shut down before the CTL response was effective.…”
Section: Discussionmentioning
confidence: 99%
“…(19,57). Limited studies to characterize the cellular responses elicited by ICP4 in mice have been performed (58,59). Martin et al (59) showed that HSVspecific T cells lysed ICP4-expressing target cells in vitro, but none of the immunized mice generated antigen-specific cytotoxic T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 In contrast to neutralizing antibodies, CTL reacts not only against envelope glycoproteins, but also against immediate-early viral proteins, which are expressed early in infection even with nonreplicative HSV-1 mutants. [35][36][37] The present study demonstrated that there was also no apparent increase in neurotoxicity caused by the inflammatory response within the spinal cord in immunized animals, but the extent of gene transfer was slightly limited. The attenuated nature as reported previously 25 was preserved in immune rats, even in rats with repeated inoculation at the same site.…”
Section: Discussionmentioning
confidence: 85%